Apathy and right caudate perfusion in idiopathic normal pressure hydrocephalus: A case‐control study. (21st December 2018) - Kanemoto, Hideki; Kazui, Hiroaki; Suehiro, Takashi; Kishima, Haruhiko; Suzuki, Yukiko; Sato, Shunsuke; Azuma, Shingo; Matsumoto, Takuya; Yoshiyama, Kenji; Shimosegawa, Eku; Tanaka, Toshihisa; Ikeda, Manabu
Abstract : Objectives: Apathy is prevalent in patients with idiopathic normal pressure hydrocephalus (iNPH), a treatable disorder resulting from ventricular enlargement. We assessed the relationship between apathy and regional cerebral blood flow (rCBF) in patients with iNPH. Methods: Before lumbo‐peritoneal shunt surgery (LPS), 56 iNPH patients were evaluated on apathy and dysphoria subscales of the Neuropsychiatric inventory (NPI), and were divided into two groups according to NPI apathy score: 15 without apathy (iNPH−APA) and 41 with apathy (iNPH+APA). Among iNPH+APA, 29 patients were evaluated for apathy and dysphoria 3 months after LPS, and were divided into two groups on the basis of the change in NPI apathy score: 13 with improvement (iNPH+ImpAPA) and 16 without improvement in apathy (iNPH−ImpAPA). N‐isopropyl‐p‐iodoamphetamine single photon emission computed tomography using the autoradiography method was performed before and after LPS, and rCBF was calculated in 22 regions of interest in the frontal cortex, basal ganglia, and limbic system. Results: In iNPH+APA, rCBF in the right caudate nuclei before LPS was significantly lower than that in iNPH−APA ( P = 0.004; two‐sample t test). Between iNPH−ImpAPA and iNPH+ImpAPA, a significant group‐by‐shunt interaction was observed for rCBF in only the right caudate nuclei (F1, 28 = 11.75, P = 0.002; two‐way repeated‐measures analysis of variance), with increased rCBF in iNPH+ImpAPA but not in iNPH−ImpAPA. The significant group‐by‐shunt interaction persisted if change in NPI dysphoria scores was used as a covariate (F1, 27 = 8.33, P = 0.008). Conclusions: Our findings suggest that right caudate dysfunction might cause apathy in iNPH patients.